Problems And Prospects Of Using Entomophages Against Pests Of Agricultural Crops - Kasimov Zafarbek; Zhumayev Rasul; Kimsanbaev Khudzhamurat (Zien Journals, 2025)
The article analyzes the problems of biological plant protection. The prospects for the development of biological plant protection in the Republic of Uzbekistan are highlighted.
Keywords: plants; biological protection; entomophage